Thermocouple: Facts and Theories - Adhikari, Krishna Raj (Himalayan Physics, 2017)
In reality, thermocouples are extremely versatile and rugged. They are primarily simple devices and can be made to very small dimensions to convert heat into electricity. They are capable of operating over a wide range of temperatures. In addition, they are low in cost and are readily interchanged or replaced. However they do need to be tacit, so that they will measure the quantity that is desired with the precision that is required. In this context, the article presents an explanation about the thermocouple. The Himalayan Physics Vol. 6 & 7, April 2017 (10-14)